PEMBELAJARAN ERA DISRUPTIF MENUJU MASYARAKAT 5.0 - Atiah, Nurma (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— Education is an entity that is very closely related to human culture and civilization. Progress in science and technology has been seen and can be enjoyed by humanity. But behind the progress of science and technology also does not have a slight negative impact on many people, especially in the current era of globalization which is very closely related to the nation's morals. The threat that may not be realized by the current generation related to the emergence of the development of science and technology is the moral degradation of the nation. Education takes a very important role in overcoming this polemic. Education is intended as a machine in creating the nation's generation to face the future and make this nation have a civilization and dignity among other nations in the world. The era that is always developing demands education to always adjust and become a motor in the process of growing up and developing the nation. In the context of globalization, education in Indonesia needs to accustom children to understand the existence of the nation in relation to the existence of other nations and all world problems. In connection with the times, we have entered what is called the era of technological disruption. In this era, demanding humans in addition to thinking logically must also be capable of addressing the development of information that has been packaged in a digital system. National education needs to consider these aspects so that the system that has been formed can be relevant to the times. The education bureaucracy at the national level needs to focus on strategic and visionary policies and be able to create a system that is able to bridge the pure values of the nation with existing developments. Keywords— Education, Nation's Morals, Era of Disruption and Globalization. Abstrak— Pendidikan merupakan suatu entitas yang sangat erat dengan budaya dan peradaban manusia. Kemajuan dalam bidang ilmu pengetahuan dan teknologi telah terlihat dan dapat dinikmati umat manusia. Namun dibalik kemajuan ilmu pengetahuan dan teknologi tersebut juga tidak sedikit menimbulkan dampak negatif bagi banyak manusia, apalagi dalam era globalisasi sekarang ini yang sangat berkaitan erat dengan moral bangsa.  Ancaman yang mungkin kurang disadari oleh generasi saat ini berkaitan dengan munculnya perkembangan ilmu pengetahuan dan teknologi adalah degradasi moral bangsa. Pendidikan mengambil peran yang sangat penting dalam mengatasi polemik yang terjadi ini. Pendidikan dimaksudkan sebagai mesin dalam menciptakan generasi bangsa untuk menghadapi masa depan dan menjadikan bangsa ini memiliki peradaban serta bermartabat di antara bangsabangsa lain di dunia. Zaman yang selalu berkembang menuntut pendidikan untuk selalu menyesuaikan diri dan menjadi motor dalam proses pendewasaan dan pembangunan bangsa. Dalam konteks globalisasi, pendidikan di Indonesia perlu membiasakan anak-anak untuk memahami eksistensi bangsa dalam kaitan dengan eksistensi bangsa-bangsa lain dan segala persoalan dunia. Berkaitan dengan perkembangan zaman, kita telah memasuki yang namanya era disrupsi teknologi. Pada era ini menuntut manusia di samping berpikir logis juga harus cakap dalam menyikapi perkembangan informasi yang telah dikemas dalam sistem digital. Pendidikan nasional perlu mempertimbangkan aspek-aspek itu sehingga sistem yang telah dibentuk dapat relefan dengan perkembangan zaman. Birokrasi pendidikan di tingkat nasional perlu fokus pada kebijakan yang strategis dan visioner serta mampu mengkreasi sistem yang mampu menjembatani antara nilai-nilai murni bangsa dengan perkembangan yang ada. Kata Kunci— Pendidikan, Moral Bangsa, Era Disrupsi dan Globalisasi